The prognostic impact of CDKN2A/B hemizygous deletions in IDH-mutant glioma - Ippen, Franziska M.; Hielscher, Thomas; Friedel, Dennis; Göbel, Kirsten; Reuss, David; Herold-Mende, Christel; Krieg, Sandro; Deimling, Andreas von; Wick, Wolfgang; Sahm, Felix; Suwala, Abigail Kora (Neuro-Oncology, 2025)
Homozygous deletions of CDKN2A/B are known to predict poor prognosis in gliomas, but the impact of hemizygous deletions is less clear. This study aimed to evaluate the prognostic significance of hemizygous CDKN2A/B deletions in IDH-mutant low-grade astrocytomas and oligodendrogliomas.Tissue samples diagnosed as astrocytoma, IDH-mutant and oligodendroglioma, IDH-mutant, 1p/19q co-deleted CNS WHO grade 2 and 3 were collected from the archives of the Institute of Neuropathology in Heidelberg. DNA methylation analysis was performed on formalin-fixed paraffin-embedded samples. Evaluation of the CDKN2A/B locus was performed by visual inspection of copy-number plots derived from methylation-array data for each case. Hemizygous and homozygous losses were assessed in relation to whole chromosomal or larger segmental losses and gains in the chromosomal profile. Survival probabilities were assessed using the Kaplan-Meier method.A total of 334 low-grade glioma cases were identified, including 173 astrocytomas and 161 oligodendrogliomas. Hemizygous deletions in CDKN2A/B (37/173 in astrocytomas, 15/161 in oligodendrogliomas) did not confer significantly worse survival outcomes compared to CDKN2A/B wild-type cases in neither low-grade astrocytoma (log-rank P = .2556; HR 2.29, 95% CI [0.76; 6.40], P = .135) nor oligodendroglioma (log-rank P = .2760; HR 0.17; 95% CI [0.01; 5.05]; P = .305), regardless of CNS WHO grade, which was further demonstrated on a subgroup of astrocytoma, IDH mutant CNS WHO 4 cases (log-rank P = .1680; HR 4.55, 95% CI [0.88; 24.51], P = .0689).Hemizygous CDKN2A/B deletions do not significantly worsen OS or progression-free survival in IDH-mutant astrocytomas and oligodendrogliomas, CNS WHO grades 2 and 3.
Veröffentlicht: 12. November 2024
Gesehen am 21.03.2025